Polypyrrole-coated Ag-based ternary capacitor composite material and preparation method thereof

Through the preparation method of polypyrrole-coated Ag-based ternary capacitor composite material, the shortcomings of existing materials in terms of conductivity, cycle stability and preparation process cost are solved, and high-performance and low-cost electrode materials are realized, which are suitable for large-scale production and long-term cycle applications of supercapacitors.

CN119694803APending Publication Date: 2025-03-25NINGDE NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411896507.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing polypyrrole/titanium dioxide/Ag ternary composites have shortcomings in conductivity, cycle stability and preparation process costs, making it difficult to achieve large-scale production and long-term cycle stability.

Method used

The preparation method of polypyrrole-coated Ag-based ternary capacitor composite material was prepared by synergistically acting between Fe3+-doped TiO2 nanoparticles and silver acetate solution, combining the reaction of pyrrole monomer and ammonium persulfate, PPy/Fe3+-TiO2/Ag composite powder was prepared, which simplified the preparation process and reduced the cost.

Benefits of technology

The capacitance performance improvement of polypyrrole/titanium dioxide/Ag ternary composite materials has been achieved, which significantly improves specific capacitance and energy density, while simplifying the preparation process and reducing production costs, making it suitable for large-scale production and long-term cycle applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119694803A_ABST
    Figure CN119694803A_ABST
Patent Text Reader

Abstract

The invention provides a polypyrrole-coated Ag-based ternary capacitor composite material. A preparation method of the polypyrrole-coated Ag-based ternary capacitor composite material comprises the following steps: preparing Fe < 3 + >-doped TiO2 nanoparticles (Fe < 3 + >-TiO2) and preparing into a solution; the preparation method comprises the following steps: adding a silver acetate solution, distilled water, a Fe < 3 + >-TiO2 solution, a FeCl3 solution and a concentrated H3PO4 solution into a reaction container, stirring, then adding a pyrrole monomer, and continuously stirring; dropwise adding an H3PO4 solution containing ammonium persulfate, stirring and filtering to obtain a PPy / Fe < 3 + >-TiO2 / Ag compound; washing the PPy / Fe < 3 + >-TiO2 / Ag compound with water and absolute ethyl alcohol, adding the PPy / Fe < 3 + >-TiO2 / Ag compound into an H3PO4 solution containing ascorbic acid, stirring to remove Fe < 3 + > in PPy particles in the PPy / Fe < 3 + >-TiO2 / Ag compound, and filtering; and washing the filtered product with water and absolute ethyl alcohol, and naturally drying to obtain the PPy / Fe < 3 + >-TiO2 / Ag powder. The material is simple in preparation process and low in cost, has excellent capacitive performance such as high specific capacity, good cycling stability and relatively high power density, and is suitable for manufacturing a capacitor electrode of a supercapacitor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a polypyrrole-coated Ag-based ternary capacitor composite material and a preparation method thereof, belonging to the technical field of capacitor materials. Background Art

[0002] As the global energy crisis and environmental problems become increasingly serious, the development of efficient and environmentally friendly energy storage devices has become a top priority. As a new type of energy storage device, supercapacitors have the advantages of fast charging and discharging speed, long cycle life, and green environmental protection. They have broad application prospects in mobile communications, electric vehicles, renewable energy and other fields. Supercapacitors are mainly composed of four parts: electrolyte solution, electrode material, current collector and diaphragm. Among them, electrode material is the core component of supercapacitors and is the most critical factor affecting the production cost and electrochemical performance of the entire supercapacitor. Therefore, research and development of high-performance, low-cost electrode materials is of great practical significance.

[0003] As a conductive polymer, polypyrrole (PPy) has the advantages of good conductivity, environmental stability, easy synthesis and low cost, and has high application value in the field of supercapacitors. However, pure polypyrrole has problems such as low conductivity and specific capacity decay during the charge and discharge process. In order to overcome these shortcomings, researchers have compounded polypyrrole with other materials to improve its electrochemical performance. Titanium dioxide (TiO2), as a typical semiconductor material, has a high specific surface area, good electrochemical stability and excellent electron transport performance. The polypyrrole / titanium dioxide composite material combines the advantages of the conductivity of polypyrrole and the high specific surface area of ​​titanium dioxide, which can effectively improve the specific capacity and cycle stability of the electrode material. The researchers have optimized the performance of the electrode material by regulating the ratio, morphology, structure and other parameters between the two. During the charge and discharge process, the polypyrrole / titanium dioxide electrode material can achieve efficient electron transport and ion adsorption, thus having a higher specific capacity. In addition, during the charge and discharge process of the polypyrrole / titanium dioxide composite material, titanium dioxide nanoparticles can effectively inhibit the volume expansion of polypyrrole and reduce the structural damage of the electrode material. Therefore, the introduction of titanium dioxide also helps to improve the structural stability of the material.

[0004] Although the polypyrrole / titanium dioxide composite system has shown good performance in the field of supercapacitors, its conductivity, cycle stability and other aspects still need to be improved. To this end, researchers have tried to introduce metals into the polypyrrole / titanium dioxide composite system in order to further improve the performance of electrode materials. Silver, as a precious metal, has good conductivity. The addition of silver nanoparticles can improve the conductivity of the polypyrrole / titanium dioxide composite material, so that the electrode material has a lower resistance during the charging and discharging process. Therefore, the polypyrrole / titanium dioxide / Ag ternary composite material has the potential to achieve a higher power density and is suitable for occasions that require fast charging and discharging.

[0005] Polypyrrole / titanium dioxide / Ag ternary composite electrode materials have significant advantages in capacitance, such as high specific capacity, good cycle stability and high power density. However, the material still has certain disadvantages in terms of conductivity, preparation process and cost. For example, the preparation process of polypyrrole / titanium dioxide / Ag ternary composite materials involves a variety of methods, such as chemical oxidation, electrochemical deposition, template synthesis, etc. These methods have high requirements for equipment and technology, resulting in complex preparation processes and difficulty in large-scale production. Silver, as a precious metal, has a high price. Although the silver content in the ternary composite material is low, it still increases the cost of the material to a certain extent. In addition, the complex preparation process also leads to high production costs. During long-term cycling, the polypyrrole / titanium dioxide / Ag ternary composite material may undergo structural changes, such as aggregation of silver nanoparticles and degradation of polypyrrole, thereby affecting the performance of the electrode material.

[0006] Therefore, it is of great practical significance to further explore the preparation method of polypyrrole / titanium dioxide / Ag ternary composite materials, optimize the preparation process parameters, and study their application performance in supercapacitors. However, there is no report on the preparation method of ideal polypyrrole / titanium dioxide / Ag ternary composite materials in the prior art. Summary of the invention

[0007] The present invention provides a polypyrrole-coated Ag-based ternary capacitor composite material and a preparation method thereof, which can effectively solve the above-mentioned problems.

[0008] The present invention is achieved in that:

[0009] A polypyrrole-coated Ag-based ternary capacitor composite material, the preparation method of which comprises: preparing Fe-doped 3+ TiO2 nanoparticles (Fe 3+ -TiO2) and prepare a solution; add silver acetate solution, distilled water, Fe 3+-TiO2 solution, FeCl3 solution and concentrated H3PO4 solution and stir, then add pyrrole monomer and continue stirring; drop H3PO4 solution containing ammonium persulfate, stir and filter to obtain PPy / Fe 3+ -TiO2 / Ag composite; washing PPy / Fe with water and anhydrous ethanol 3+ -TiO2 / Ag composite, PPy / Fe 3+ -TiO2 / Ag composite was added to H3PO4 solution containing ascorbic acid and stirred to remove PPy / Fe 3+ -Fe in PPy particles in TiO2 / Ag composites 3+ , and then filter; wash the filtered product with water and anhydrous ethanol, and wait until it is naturally dried to obtain PPy / Fe 3+ -TiO2 / Ag powder.

[0010] In some embodiments, the PPy / Fe 3+ -The particle size of TiO2 / Ag powder is 60-80nm.

[0011] A method for preparing the polypyrrole-coated Ag-based ternary capacitor composite material comprises the following steps:

[0012] S1, adding distilled water, anhydrous ethanol, ethylene glycol, FeCl3 solution and hydrochloric acid to a reaction container to prepare a mixed solution; mixing tetrabutyl titanate and ethylene glycol, gradually adding the mixture, continuously stirring and performing a first hydrothermal reaction, centrifuging the product, washing it with anhydrous ethanol, and filtering; adding the filtered product to a NaOH solution, stirring evenly, performing a second hydrothermal reaction, centrifuging the product, washing it with anhydrous ethanol, and filtering it; dissolving the filtered product in water to obtain Fe 3+ -TiO2 solution;

[0013] S2, add silver acetate solution, distilled water, Fe prepared in step S1 into the reaction vessel. 3+ -TiO2 solution, FeCl3 solution and concentrated H3PO4 solution and stir, then add pyrrole monomer and continue stirring; drop H3PO4 solution containing ammonium persulfate, stir and filter to obtain PPy / Fe 3+ -TiO2 / Ag composite; washing PPy / Fe with water and anhydrous ethanol 3+ -TiO2 / Ag composite, PPy / Fe 3+ -TiO2 / Ag composite was added to H3PO4 solution containing ascorbic acid and stirred to remove PPy / Fe 3+ -Fe in PPy particles in TiO2 / Ag composites 3+, and then filter; wash the filtered product with water and anhydrous ethanol, and wait until it is naturally dried to obtain PPy / Fe 3+ -TiO2 / Ag powder, that is, the polypyrrole-coated Ag-based ternary capacitor composite material.

[0014] In some embodiments, the Fe 3+ -Fe in TiO2 solution 3+ The doping level in TiO2 nanoparticles is 8-12 wt%.

[0015] In some embodiments, in step S1, the concentration of the FeCl3 solution is 0.05-0.2 mol / L, and the concentration of hydrochloric acid is 0.8-1.2 M; the ratio of the distilled water, anhydrous ethanol, ethylene glycol, FeCl3 solution and hydrochloric acid is 5-10 mL: 10-20 mL: 10-20 mL: 80-120 μL: 0.5-1.5 mL, and the ratio of tetrabutyl titanate to ethylene glycol is 3-5 mL: 2-4 mL.

[0016] In some embodiments, in step S2, the concentration of the silver acetate solution is 40-60 mmol / L, and the concentration of the FeCl3 solution is 0.05-0.2 mol / L; the silver acetate solution, distilled water, Fe 3+ -The ratio of TiO2 solution, FeCl3 solution and pyrrole monomer is 1-2mL:40-60mL:0.05-0.2mL:80-120μL:180-220μL.

[0017] In some embodiments, in step S1, the temperature of the first hydrothermal reaction is 70-80°C, and the time is 22-26 hours; the temperature of the second hydrothermal reaction is 145-155°C, and the time is 22-26 hours.

[0018] A method for preparing a capacitor electrode based on a polypyrrole-coated Ag-based ternary capacitor composite material, characterized in that it comprises the following steps: using Nafion as a binder, 3+ -TiO2 / Ag powder material is loaded on the glassy carbon electrode.

[0019] A capacitor electrode based on a polypyrrole-coated Ag-based ternary capacitor composite material prepared according to the above method.

[0020] An electrochemical testing method for a capacitor electrode based on a polypyrrole-coated Ag-based ternary capacitor composite material, wherein the capacitor electrode is used as a working electrode, a graphite electrode is used as a counter electrode, a saturated calomel electrode (SCE) is used as a reference electrode, and an electrochemical workstation (CHI660D) is used to perform cyclic voltammetry (CV) and constant current charge and discharge (GCD) tests in a 1M Na2SO4 solution. The CV test voltage range is -0.5V-0.5V (vs. SCE), and the current density of the GCD test is 2-20A / g.

[0021] An application of the above-mentioned polypyrrole-coated Ag-based ternary capacitor composite material in the manufacture of supercapacitors.

[0022] The beneficial effects of the present invention are:

[0023] The invention provides a polypyrrole-coated Ag-based ternary capacitor composite material, which has a simple preparation process, low cost and can achieve large-scale production.

[0024] The present invention discloses a polypyrrole-coated Ag-based ternary capacitor composite material, wherein PPy, Fe 3+ Doped TiO2(Fe 3+ -TiO2) and Ag ternary components make PPy / Fe 3+ -The capacitance performance of TiO2 / Ag ternary composite electrode has been significantly improved. 3+ Doping can effectively increase the electron transport properties of TiO2, so that the specific capacitance of the composite material is significantly increased. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0026] Figure 1 For PPy(a), PPy / Ag(b), PPy / Fe 3+ -TiO2(c), PPy / Fe 3+ -SEM image of the surface morphology of TiO2 / Ag(d) composite material.

[0027] Figure 2 For PPy(a), PPy / Ag(b), PPy / Fe 3+ -TiO2(c), PPy / Fe 3+-CV curves of TiO2 / Ag(d) series electrodes at different scanning rates in 1MNa2SO4 solution.

[0028] Figure 3 PPy, PPy / Ag, PPy / Fe 3+ -TiO2, PPy / Fe 3+ -CV curves of TiO2 / Ag series electrodes in 1MNa2SO4 solution.

[0029] Figure 4 PPy, PPy / Ag, PPy / Fe 3+ -TiO2, PPy / Fe 3+ -The relationship between specific capacity and scan rate when the TiO2 / Ag series electrodes were subjected to cyclic voltammetry test in 1MNa2SO4 solution.

[0030] Figure 5 For PPy(a), PPy / Ag(b), PPy / Fe 3+ -TiO2(c), PPy / Fe 3+ -GCD curves of TiO2 / Ag(d) series electrodes at different current densities in 1MNa2SO4 solution.

[0031] Figure 6 PPy, PPy / Ag, PPy / Fe 3+ -TiO2, PPy / Fe 3+ -GCD curve of TiO2 / Ag series electrodes at 2A / g current density in 1MNa2SO4 solution.

[0032] Figure 7 PPy, PPy / Ag, PPy / Fe 3+ -TiO2, PPy / Fe 3+ -Charge and discharge performance test of TiO2 / Ag series electrodes in 1MNa2SO4 solution, showing the relationship between energy density and current density. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the invention claimed for protection, but merely represents the selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0034] Example 1 PPy / Fe 3+ -Preparation of TiO2 / Ag powder:

[0035] (1) Fe doping 3+ TiO2 nanoparticles (Fe 3+ -TiO2) and solution preparation

[0036] First, mix 7mL of pure water, 14mL of anhydrous ethanol, 14mL of ethylene glycol, 100μL of 0.1mol / L FeCl3 solution and 1mL of 1M HCl. Then, mix 4.25mL of tetrabutyl titanate with 3mL of ethylene glycol, gradually add it to the mixed solution in the first step, and continue stirring at 75 degrees Celsius for 24 hours. After that, centrifuge and wash with anhydrous ethanol. Use 0.5M NaOH to prepare the product into a solution with a mass fraction of 10%. After hydrothermal treatment at 150 degrees Celsius for 24 hours, centrifuge, filter, and wash with anhydrous ethanol, finally dissolve the product in water to obtain 10% Fe 3+ -TiO2 aqueous solution.

[0037] (2)PPy / Fe 3+ -Preparation of TiO2 / Ag powder

[0038] Add 1.125 mL of 47.93 mM silver acetate solution to a 250 mL flat-bottom flask, add 50 mL of pure water and mix well, then add 0.1 mL of 10% Fe 3+ -TiO2 solution, 100 μL 0.1M FeCl3 solution and 2 mL concentrated H3PO4 were added and stirred for 0.5 hours, 200 μL pyrrole monomer was added to the solution and stirred for 2 hours. 0.3 g ammonium persulfate was added to 5 mL 10 wt% H3PO4, mixed and then slowly dripped into the solution prepared in the previous step, stirred for 1 hour and filtered to obtain PPy / Fe3+ -TiO2 / Ag composite. Wash PPy / Fe with water and anhydrous ethanol 3+ -TiO2 / Ag composite, add it into 50mL 2wt% H3PO4 (containing 100mM sodium chloride) and stir for 24 hours to remove PPy / Fe 3+ -Fe in PPy particles in TiO2 / Ag composites 3 + The product was filtered, washed with water and anhydrous ethanol, and dried naturally to obtain PPy / Fe 3+ -TiO2 / Ag powder.

[0039] Comparative Example 1 Preparation of PPy powder

[0040] In a 250mL flask, mix 100μL of 0.1M FeCl3 solution, 2mL of concentrated H3PO4 and 50mL of pure water, and stir for 0.5 hours. Then add 200μL of pyrrole monomer and continue stirring for 2 hours. Next, add 0.3g of ammonium persulfate to 5mL of 10wt% H3PO4, mix well, slowly add to the previous mixture, stir for 1 hour and filter. Wash the filter cake with water and anhydrous ethanol, and stir in 50mL of 2wt% H3PO4 containing 100mM sodium hypochlorite for 24 hours; EDS detection proves that this step removes Fe in PPy. 3+ After filtering, washing and drying under natural conditions, PPy powder was obtained.

[0041] Comparative Example 2PPy / Fe 3+ -Preparation of TiO2 powder

[0042] In a 250 mL flask, mix 0.1 mL of 10% Fe 3+ -TiO2 solution, 100μL 0.1M FeCl3 solution, 2mL concentrated H3PO4 and 50mL pure water, stir for 0.5 hours. Add 200μL of pyrrole monomer and stir for 2 hours. Add 0.3g of ammonium persulfate to 5mL 10wt% H3PO4, stir evenly and add dropwise to the previous solution, continue stirring for 1 hour and filter. Wash the filter cake with water and anhydrous ethanol, and stir in 50mL 2wt% H3PO4 containing 100mM sodium hypochlorite for 24 hours to remove Fe in PPy. 3+ , and at this time, Fe is doped in TiO2 3+ After filtration, washing and drying under natural conditions, PPy / Fe 3+ -TiO2 composite powder.

[0043] Comparative Example 3 Preparation of PPy / Ag powder

[0044] Add 1.125mL 47.93mM silver acetate solution to a 250mL flat-bottomed flask, add 50mL pure water and mix well, then add 100μL 0.1M FeCl3 solution and 2mL concentrated H3PO4 and stir for 0.5 hours, then add 200μL pyrrole monomer to the solution and stir for 2 hours. Add 0.3g ammonium persulfate to 5mL 10wt% H3PO4, and after the solution is mixed, slowly drip it into the solution prepared in the previous step, stir for 1 hour and filter. Wash the filtered product with water and anhydrous ethanol, add it to 50mL 2wt% H3PO4 (containing 100mM sodium hypochlorite) and stir for 24 hours to remove Fe in the sample. 3+ The product was filtered, washed with water and anhydrous ethanol, and dried naturally to obtain PPy / Ag powder.

[0045] Characterization Test

[0046] Figure 1 The surface morphology of the prepared material is shown in SEM image. Figure 1 (a) It can be seen that the PPy prepared using the above experimental method is an irregular spherical particle with a particle size of about 200-300nm. Figure 1 As can be seen in (b), when Ag and PPy are composited, PPy is coated on the outer layer of Ag, and the diameter of the coated Ag nanoparticles is 30-60nm; the diameter of the PPy / Ag composite particles is significantly increased, about 400-500nm irregular spherical particles. EDS test results show that the PPy and PPy / Ag particles synthesized by this method do not contain Fe 3+ .from Figure 1 In (c), it can be observed that PPy composite Fe 3+ -TiO2, the particle size of PPy becomes significantly smaller, and the particle size is 40-60nm irregular spherical particles; Fe 3+ -TiO2 is irregular spherical particles less than 10nm and attached to the surface of PPy. Figure 1 It can be found in (d) that after being composited with Ag, PPy / Fe 3+ -The particle size of PPy-based particles in TiO2 / Ag composites is compared with that of PPy / Fe 3+ -TiO2 has no obvious change and is an irregular spherical particle with a particle size of about 60-80nm; in this ternary composite material, Ag is an irregular particle with a diameter less than 20nm and is coated inside PPy, and Fe is less than 10nm in diameter. 3+ -TiO2 attached to the surface of PPy / Ag composite particles; this result shows that the synthesis method of the ternary composite material effectively reduces the diameter of the composite particles and increases the surface area. EDS test results show that in the composite particles PPy / Fe 3+-TiO2 and PPy / Fe 3+ -Fe doped in TiO2 / Ag was detected 3+ The XRD test results show that the doped Fe 3+ The form of Fe2O3 is doped in anatase TiO2 particles.

[0047] Application Examples

[0048] Preparation of capacitor electrodes

[0049] PPy, PPy / Ag, PPy / Fe prepared in Example 1 and Comparative Examples 1-3 3+ -TiO2, PPy / Fe 3+ -TiO2 / Ag powder, with Nafion as binder, is loaded on a glassy carbon electrode with a diameter of 5 mm.

[0050] Electrochemical testing of capacitor electrodes

[0051] Electrochemical experiments were performed using the capacitor electrode made of the composite material powder obtained in Example 1 and Comparative Examples 1-3 as the working electrode, the graphite electrode as the counter electrode, and the saturated calomel electrode (SCE) as the reference electrode. Cyclic voltammetry (CV) and constant current charge-discharge (GCD) tests were performed in 1M Na2SO4 solution using an electrochemical workstation (CHI660D). The CV test voltage range was -0.5V-0.5V (vs. SCE), and the GCD test current density was 2-20A / g. The electrochemical test results are shown in Tables 1 and Figure 2-7 shown.

[0052] Table 1 PPy / Fe 3+ -Specific capacitance and energy density of TiO2 / Ag series electrodes in 1M Na2SO4 solution

[0053]

[0054] Table 1 clearly shows the specific capacitance and energy density data of the prepared materials. Under the condition of scanning speed of 5mV / s, the specific capacitance of the electrode material after PPy coated with Ag nanoparticles did not increase significantly. 3+ -TiO2 composite electrode material specific capacitance increased by 96.3%, while PPy combined with Ag and Fe 3+ -TiO2 composite electrode material increased its specific capacitance by 148.8%. 3+ The synergistic effect between the ternary composite material formed by -TiO2 and PPy effectively enhances the specific capacitance of the composite system. At a current density of 2A / g, it can be seen that PPy and Ag or Fe 3+-TiO2 composite, the energy density of the electrode material increased by 3% and 110% respectively, while with Ag and Fe 3+ -TiO2 composite, the energy density increased by 188%, this data once again confirmed the 3+ -The synergistic effect between TiO2 and Ag can effectively improve the electrochemical performance of electrode materials.

[0055] Figure 2 The CV curves of the obtained materials at different scan rates in 1M Na2SO4 solution, with the test voltage at -0.5V-0.5V (vs. SCE). By comparison, it can be found that with the increase of CV scan rate, the current density of all electrode materials increases. At the same scan rate, we can find that the current density of PPy is lower. When PPy and Ag form a binary composite material, its current density does not change significantly; when PPy and Fe 3+ -TiO2 forms a binary composite material, its current density is significantly improved; when PPy is combined with Ag, Fe 3+ -TiO2 forms a ternary composite material, the current density is the largest. The results show that the prepared Fe-loaded 3+ -TiO2 particles and polypyrrole coated with Ag nanoparticles showed excellent capacitive properties.

[0056] Figure 3 The CV curve of the prepared material in 1M Na2SO4 solution, the scanning rate is 50mV / s. It can be found from the figure that at 0.2V voltage, PPy, PPy / Ag, PPy / Fe 3+ -TiO2 and PPy / Fe 3+ The current density of the TiO2 / Ag electrode material is 6.2A / g, 5.7A / g, 10.4A / g and 14A / g respectively. Compared with PPy, the current density of the PPy / Ag binary composite material has not changed significantly, indicating that although coating Ag nanoparticles alone can improve the conductivity of PPy, it cannot significantly improve the specific capacitance of PPy. 3+ -The current density of the TiO2 binary composite material is significantly improved compared with PPy, which is 1.68 times that of PPy, indicating that the ... which is 3+ -TiO2 composite significantly increased the specific capacitance of PPy. In addition, it was found during the test that PPy / Fe 3+ -TiO2 binary composite material has significantly enhanced electron transfer rate and faster electrochemical response; cycle stability test shows that Fe 3+ -TiO2 nanoparticles can effectively inhibit the volume expansion of PPy, reduce the structural damage of electrode materials, and help improve the structural stability of materials.3+ Compared with the capacitance performance of PPy / TiO2 binary composite materials, the undoped Fe 3+ The current density of the PPy / TiO2 binary composite material under the same conditions is only 1.35 times that of PPy, indicating that Fe 3+ The doping of PPy / Fe can effectively increase the electron transport performance of TiO2, which significantly increases the specific capacitance of the composite material. 3+ -TiO2 binary composite material is compounded with Ag, PPy / Fe 3+ -TiO2 / Ag ternary composite electrode material has the highest current density, which is PPy / Fe 3+ -TiO2 is 1.35 times that of the composite, indicating that the composite of Ag particles effectively enhances the conductivity of the PPy composite material and thus effectively improves its specific capacitance. By comparing the capacitance performance of PPy / Ag, it can be found that the enhancement of the capacitance performance of the composite system by Ag nanoparticles requires the third component Fe 3+ -TiO2 effective composite, which can prove that PPy, Fe 3+ -The synergistic effect of TiO2 and Ag ternary components makes PPy / Fe 3+ -The capacitive performance of the TiO2 / Ag ternary composite electrode has been significantly improved.

[0057] Figure 4 The relationship curve between specific capacity and scanning speed when the prepared material was subjected to CV test in 1M Na2SO4 solution. From the figure, it can be seen that when the scanning rate is 5mV / s, the specific capacitance of PPy is 455F / g. Compared with PPy, the specific capacitance of the composite electrode material coated with Ag nanoparticles is 447F / g; while the composite Fe 3+ -The specific capacitance of TiO2 electrode material increased to 888F / g, an increase of 96.3%. When the electrode material is composited with Ag and Fe 3+ -TiO2, the specific capacitance increased to 1132F / g, an increase of 148.8%. 3+ -TiO2 particles and Ag nanoparticles coated polypyrrole ternary composite materials have significant advantages in specific capacitance performance.

[0058] Figure 5 The GCD curve of the prepared material in 1M Na2SO4 solution at a current density of 2-20A / g. It can be observed that the single charge and discharge time of PPy is the shortest, while the single charge and discharge time of the PPy composite material coated with Ag nanoparticles is close to that of PPy; 3+ -TiO2 PPy material has a significantly longer charge and discharge time; at the same time, it is coated with Ag nanoparticles and loaded with Fe 3+ -PPy / Fe of TiO23+ -The increase in single charge and discharge time of TiO2 / Ag ternary composite material is the most significant. This result is consistent with the CV test results.

[0059] Figure 6 The GCD curve of the prepared material in 1M Na2SO4 solution at a current density of 2A / g. It can be found that under the condition of 2A / g, the single charge and discharge time of PPy is 100s. When PPy is composited with Ag, the single charge and discharge time is extended to 106s, while when it is composited with Fe 3+ -TiO2 composite, the single charge and discharge time was further extended to 206s, an increase of 6% and 106% respectively. 3+ -When TiO2 and Ag are combined at the same time, the single charge and discharge time increases significantly to 293s, an increase of 193%, which indicates that the prepared PPy / Fe 3+ -TiO2 / Ag ternary composite material has the best capacitor performance.

[0060] Figure 7 The relationship between specific capacity and current density of the prepared material in the GCD test in 1M Na2SO4 solution is shown. It shows that at a current density of 2A / g, the energy density of the PPy electrode material is 12.7Wh / kg. 3+ -TiO2 composite, the formed PPy / Ag and PPy / Fe 3+ -TiO2 binary composite electrode materials have increased their energy density to 13.1Wh / kg and 26.7Wh / kg respectively. 3+ -The energy density of TiO2 / Ag ternary composite electrode material has been increased to 36.6Wh / kg. This result clearly shows that the prepared Fe-loaded 3+ -TiO2 particles and Ag nanoparticles coated polypyrrole ternary composite materials have significant advantages in energy density.

[0061] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A polypyrrole-coated Ag-based ternary capacitor composite material, characterized in that: The preparation method comprises: preparing Fe-doped 3+ TiO2 nanoparticles Fe 3+ -TiO2 and prepare a solution; add silver acetate solution, distilled water, Fe 3+ -TiO2 solution, FeCl3 solution and concentrated H3PO4 solution and stir, then add pyrrole monomer and continue stirring; drop H3PO4 solution containing ammonium persulfate, stir and filter to obtain PPy / Fe 3+ -TiO2 / Ag composite; washing PPy / Fe with water and anhydrous ethanol 3 + -TiO2 / Ag composite, PPy / Fe 3+ -TiO2 / Ag composite was added to H3PO4 solution containing ascorbic acid and stirred to remove PPy / Fe 3+ -Fe in PPy particles in TiO2 / Ag composites 3+ , and then filter; wash the filtered product with water and anhydrous ethanol, and wait until it is naturally dried to obtain PPy / Fe 3+ -TiO2 / Ag powder.

2. The polypyrrole-coated Ag-based ternary capacitor composite material according to claim 1, characterized in that: The PPy / Fe 3+ -The particle size of TiO2 / Ag powder is 60-80nm.

3. A method for preparing the polypyrrole-coated Ag-based ternary capacitor composite material according to claim 1 or 2, characterized in that: The following steps are involved: S1, adding distilled water, anhydrous ethanol, ethylene glycol, FeCl3 solution and hydrochloric acid into a reaction container to prepare a mixed solution; mixing tetrabutyl titanate and ethylene glycol, gradually adding the mixture to the mixed solution, continuously stirring and performing a first hydrothermal reaction, centrifuging and separating the product, washing with anhydrous ethanol, and filtering; The filtered product was added to the NaOH solution, stirred evenly, and then subjected to the second hydrothermal reaction. The product was then separated by centrifugation, washed with anhydrous ethanol, and filtered again. The filtered product was dissolved in water to obtain Fe 3+ -TiO2 solution; S2, add silver acetate solution, distilled water, Fe prepared in step S1 into the reaction vessel. 3+ -TiO2 solution, FeCl3 solution and concentrated H3PO4 solution and stir, then add pyrrole monomer and continue stirring; drop H3PO4 solution containing ammonium persulfate, stir and filter to obtain PPy / Fe 3+ -TiO2 / Ag composite; washing PPy / Fe with water and anhydrous ethanol 3+ -TiO2 / Ag composite, PPy / Fe 3+ -TiO2 / Ag composite was added to H3PO4 solution containing ascorbic acid and stirred to remove PPy / Fe 3+ -Fe in PPy particles in TiO2 / Ag composites 3+ , and then filter; wash the filtered product with water and anhydrous ethanol, and wait until it is naturally dried to obtain PPy / Fe 3+ -TiO2 / Ag powder, that is, the polypyrrole-coated Ag-based ternary capacitor composite material.

4. The preparation method according to claim 3, characterized in that: The Fe 3+ -Fe in TiO2 solution 3+ The doping level in TiO2 nanoparticles is 8-12 wt%.

5. The preparation method according to claim 3, characterized in that: In step S1, the concentration of the FeCl3 solution is 0.05-0.2 mol / L, and the concentration of hydrochloric acid is 0.8-1.2 M; the ratio of distilled water, anhydrous ethanol, ethylene glycol, FeCl3 solution and hydrochloric acid is 5-10 mL: 10-20 mL: 10-20 mL: 80-120 μL: 0.5-1.5 mL, and the ratio of tetrabutyl titanate to ethylene glycol is 3-5 mL: 2-4 mL; In step S2, the concentration of the silver acetate solution is 40-60 mmol / L, and the concentration of the FeCl3 solution is 0.05-0.2 mol / L; the silver acetate solution, distilled water, Fe 3+ -The ratio of TiO2 solution, FeCl3 solution and pyrrole monomer is 1-2mL:40-60mL:0.05-0.2mL:80-120μL:180-220μL.

6. The preparation method according to claim 3, characterized in that: In step S1, the temperature of the first hydrothermal reaction is 70-80°C and the time is 22-26 hours; the temperature of the second hydrothermal reaction is 145-155°C and the time is 22-26 hours.

7. A method for preparing a capacitor electrode based on a polypyrrole-coated Ag-based ternary capacitor composite material according to claim 1 or 2, characterized in that: The following steps are involved: Using Nafion as binder, PPy / Fe 3+ -TiO2 / Ag powder material is loaded on the glassy carbon electrode.

8. A capacitor electrode based on a polypyrrole-coated Ag-based ternary capacitor composite material prepared according to the method of claim 7.

9. An electrochemical testing method for capacitor electrodes based on polypyrrole-coated Ag-based ternary capacitor composite materials according to claim 8, characterized in that: The capacitor electrode is used as the working electrode, the graphite electrode is used as the counter electrode, and the saturated calomel electrode SCE is used as the reference electrode. An electrochemical workstation is used to carry out cyclic voltammetry (CV) test and constant current charge and discharge (GCD) test in a Na2SO4 solution. The voltage range of the CV test is -0.5V-0.5V, and the current density of the GCD test is 2-20A / g.

10. Use of the polypyrrole-coated Ag-based ternary capacitor composite material according to claim 1 or 2 in manufacturing supercapacitors.